Kepuasan Konsumen dan Strategi EWOM dalam Meningkatkan Loyalitas Konsumen Produk Boba pada Generasi Z - Sarinastiti, Kania; Sulistiobudi, Rezki Ashriyana (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Boba is currently one of the favorite products consumed by generation Z. Popularity of boba products can be seen from the purchases level of boba and how it is viral on the internet such as Instagram, twitter, Zomato, or food blogs. The spread on the internet is called electronic wordof-mouth (EWOM). One of the factors that increase EWOM is customer satisfaction. The study was conducted to explain the relationship between customer satisfaction and EWOM using the correlation study method. This study involved 111 respondents. The sample characteristics are students who have bought boba and have posts about boba in the internet. The consumer satisfaction measurement tool was adapted from Martín Consuegra et al. (2007).. Meanwhile, the EWOM measuring instrument was adapted from the Jeong and Jang (2011). The results show that there is a significant relationship between customer satisfaction and EWOM. The higher the consumer satisfaction, the higher the spread of positive EWOM regarding boba products. Results also show that women do the spread of EWOM higher because satisfaction encourages their desire to promote their favorite boba products to others. Consumers who have deployed EWOM can increase loyalty to the products used because consumers experience high satisfaction with their products. Sellers can increase consumers’ loyalty by paying attention to the product quality and service so that consumers feel satisfied with the products used and disseminate the product information.